Experimental and numerical study of undersized shear panel dampers with bolted connections. (1st April 2023) - Zhao, Huatian; Shi, Gang; Li, Shuailing; Zhang, Naizhou; Zhuang, Shanxiang; Zhu, Bin
Highlights: An undersized shear panel damper with bolted connections was developed. Four specimens were designed and tested under cyclic loading. Hysteresis behaviour and mechanical indexes were evaluated. FE models considering ultralow cycle fatigue fracture were developed and validated against test results. Abstract: Shear panel dampers have been widely utilised in steel structures to enhance structural damping and dissipate earthquake energy, and thus minimise damage to primary structures. These shear panel dampers commonly feature relatively large sizes and high loading resistance owing to their main applications in multi-storey and high-rise buildings. In contrast, this study intended to develop an undersized shear panel damper (USPD) for prefabricated low-rise structures without site welding. To investigate the cyclic behaviour and fracture characteristics, USPDs made of Q235 low-carbon steel were designed as full-scale specimens with bolted connections and then tested under cyclic shear loads. Moreover, finite element (FE) models were established by considering the material and geometric nonlinearities. The ultralow cycle fatigue (ULCF) fracture initiation life of the USPDs was further predicted based on the cyclic void growth model (CVGM) and validated against the test results. Accordingly, the USPDs exhibited plump and stable hysteresis curves before crack propagating severely and featured significant cyclic hardening behaviour, where the ultimate-to-yield resistance ratio ranged from 2.20 to 2.45. The presented FE models could simulate the cyclic behaviour of USPDs well, and the CVGM accurately predicted the ULCF fracture initiation life with the average discrepancy of 14.8%. The results demonstrate the potential applicability of USPDs, and the developed FE analysis method considering ULCF fractures provides a solution for further configuration optimisations and parametric analyses, reducing the cost of experimental studies.